The mediating role of customer satisfaction in the relationship between service quality and customer loyalty / Kamisah Ismail, Jamie Wan Chiou Tin and Jacinta Phooi M’ng Chan - Ismail, Kamisah; Wan, Jamie Chiou Tin; Phooi, Jacinta M’ng Chan (UiTM Press, 2021)
The purpose of this paper is to examine the relationships between service quality, customer satisfaction and customer loyalty in the context of the life insurance business. The Theory of Planned Behaviour was used in constructing the framework which measured service quality. The questionnaire survey method was used to obtain data related to the perception of life insurance policy holders towards their current insurance company. The analysis of 150 life insurance policy holders using multiple regression and SOBEL test showed that customer satisfaction plays a mediating role in the relationship between service quality and customer loyalty. In other words, the effect of mediation is present where service quality gives a positive impact on customer satisfaction, which subsequently gives a positive impact on customer loyalty. Further analysis also revealed that among the five dimensions in the SERVQUAL model, reliability played the most important role in determining customer satisfaction and customer loyalty. The outcome drawn from the current study offers insights for the insurance industry to focus on the dimensions that play a significant role in retaining and capturing more loyal customers. This will assist businesses in gaining profitability and sustainability.